(untitled) (Herald of the National Children’s Medical Center, 2025)
Acute renal failure (ARF) is a sudden impairment of kidney function that significantly worsens a child’s condition. Mortality in acute renal failure varies from 3-5% in hemolytic-uremic syndrome to 30-70% in sepsis and multiple organ failure. Circadian blood pressure (BP) disorders in children with acute renal failure remain insufficiently studied, especially taking into account age differences.